Infrared fluorescent imaging as a potent tool for in vitro, ex vivo and in vivo models of visceral leishmaniasis. - Estefanía Calvo-Álvarez; Kostantinos Stamatakis; Carmen Punzón; Raquel Álvarez-Velilla; Ana Tejería; José Miguel Escudero-Martínez; Yolanda Pérez-Pertejo; Manuel Fresno; Rafael Balaña-Fouce; Rosa M Reguera (Public Library of Science (PLoS), 2015)
BACKGROUND:Visceral leishmaniasis (VL) is hypoendemic in the Mediterranean region, where it is caused by the protozoan Leishmania infantum. An effective vaccine for humans is not yet available and the severe side-effects of the drugs in clinical use, linked to the parenteral administration route of most of them, are significant concerns of the current leishmanicidal medicines. New drugs are desperately needed to treat VL and phenotype-based High Throughput Screenings (HTS) appear to be suitable to achieve this goal in the coming years. METHODOLOGY/PRINCIPAL FINDINGS:We generated two infrared fluorescent L. infantum strains, which stably overexpress the IFP 1.4 and iRFP reporter genes and performed comparative studies of their biophotonic properties at both promastigote and amastigote stages. To improve the fluorescence emission of the selected reporter in intracellular amastigotes, we engineered distinct constructs by introducing regulatory sequences of differentially-expressed genes (A2, AMASTIN and HSP70 II). The final strain that carries the iRFP gene under the control of the L. infantum HSP70 II downstream region (DSR), was employed to perform a phenotypic screening of a collection of small molecules by using ex vivo splenocytes from infrared-infected BALB/c mice. In order to further investigate the usefulness of this infrared strain, we monitored an in vivo infection by imaging BALB/c mice in a time-course study of 20 weeks. CONCLUSIONS/SIGNIFICANCE:The near-infrared fluorescent L. infantum strain represents an important step forward in bioimaging research of VL, providing a robust model of phenotypic screening suitable for HTS of small molecule collections in the mammalian parasite stage. Additionally, HSP70 II+L. infantum strain permitted for the first time to monitor an in vivo infection of VL. This finding accelerates the possibility of testing new drugs in preclinical in vivo studies, thus supporting the urgent and challenging drug discovery program against this parasitic disease.